Ritual Language and Social Meaning in Tiwah: A Semiotics Study - Qalyubi, Imam; Misrita, Misrita; Li, Huli (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
Despite extensive scholarship on ritual symbolism, studies of Indonesian indigenous rituals have largely treated material objects as culturally meaningful entities without explaining how their meanings are structurally produced, authorized, and stabilized within ritual systems. In particular, the application of Roland Barthes’ structural semiotics to ritual language remains underdeveloped. This study investigates how linguistic authorization functions as a mechanism of semiotic closure through which material objects acquire ritual efficacy within a structured sign system. Employing a qualitative ethnographic design, data were collected through participant observation, interviews with ritual specialists (Basir and Telun), and documentation of ritual utterances and material practices in the Tiwah mortuary ceremony among Kaharingan adherents in Central Kalimantan. The analysis applies Barthes’ Expression-Relation-Content (E-R-C) framework to trace how denotative meanings are transformed into culturally regulated connotations through ritual sequencing and authorized speech. The findings demonstrate that ritual objects do not possess inherent efficacy; rather, their meanings emerge from the structured alignment of material form, ritual position, and linguistically sanctioned authority. Gold (bulau) is reconstituted from a precious metal into a cosmological mediator, while rice (behas) functions as a relational semiotic resource whose meaning is generated through ordered deployment and sequential address. By foregrounding linguistic authorization as a structural mechanism that stabilizes connotation and limits interpretive variability, this study extends Barthesian structural semiotics and offers a transferable analytical model for examining how ritual meaning is produced and governed across diverse cultural contexts of ritual language and symbolism.